Integron types, gene cassettes and antimicrobial resistance profile of Acinetobacter baumannii isolated from BAL samples in Babol, north of Iran. (August 2017) - Akrami, Fariba; Shahandashti, Elaheh Ferdosi; Yahyapour, Yousef; Sadeghi, Mohsen; Khafri, Soraya; Pournajaf, Abazar; Rajabnia, Ramazan
Abstract: Multi-drug resistant isolates of Acinetobacter baumannii have created therapeutic problems worldwide. This current study was intended to determine the Integron types, gene cassettes and antimicrobial resistance profile of A. baumannii isolated from BAL samples in Babol, north of Iran. During a 15-month period, 35 A. baumannii isolates were studied. Different classes of antimicrobial agents were used to determine the resistance ratios. Multiplex-PCR was used to detect different types of integrons and associated gene cassettes. The resistance rates to GM, FEP, AK, TOB, CP, PIP, SAM, IPM, SXT, CTX, CAZ, CL, TIM, MEM, and TZP were 85.7%, 100%, 91.4%, 68.5%, 94.3%, 88.5%, 97.1%, 94.3%, 100%, 100%, 100%, 0.0%, 91.4%, 94.3% and 91.4%, respectively. The distribution analysis of int genes showed that 25.7%, 88.6% and 28.6% of isolates carried the intI, intII and intIII genes, respectively. The prevalence of aadB, dfrA1, bla-OXA 30 and aadA1 genes were 94.3%, 77.1%, 40% and 5.7%, respectively. The current study showed that a high level of A. baumannii isolates harbor integrons in our therapeutic center, which may lead to distribution of multiple antimicrobial resistance. The different types of gene cassette arrays in the present study highlight the important role of geographical features in MDR isolates dissemination which could be credited to different profiles of drug consumption in different areas. The findings emphasized that the need for continuous surveillance to prevent distribution of multidrug resistance among A. baumannii strains in Iran. Highlights: This work highlighted the integron types, gene cassettes and antimicrobial resistance profile of A. baumannii isolated from BAL samples in Babol, north of Iran. Relation between antimicrobial resistance and gene cassettes. Multidrug resistance is increasingly reported among A. baumannii clinical isolates.